2017
DOI: 10.21577/0100-4042.20170004
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual DFT Study of the Chemical Reactivity of Magnesium Octaethylporphyrin (MgOEP) as Predicted by the Minnesota Family of Density Functionals

Abstract: The Minnesota family of density functionals has been assessed for the calculation of the molecular structure and electronic properties of a Mg(II)-porphyrin, namely Magnesium Octaethylporphyrin (MgOEP). Several global descriptors arising from Conceptual DFT have been calculated through a ∆SCF procedure, and by means of the HOMO and LUMO frontier orbitals. On the basis of the obtained Conceptual DFT indices, a series of descriptors have been devised in order to verify the fulfillment of the "Koopmans' theorem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Consistent with the work presented earlier [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], this study involved performing computational studies with the Gaussian 09 series of programs [ 64 ] whose density functional methods are implemented in the computational package. The gradient technique was relied upon to determine the equilibrium geometries of the molecules; whereas the determination of the force constants and vibrational frequencies involves computing analytical frequencies on various stationary points that are obtained as optimization is completed to check whether the minima were real.…”
Section: Settings and Computational Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with the work presented earlier [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], this study involved performing computational studies with the Gaussian 09 series of programs [ 64 ] whose density functional methods are implemented in the computational package. The gradient technique was relied upon to determine the equilibrium geometries of the molecules; whereas the determination of the force constants and vibrational frequencies involves computing analytical frequencies on various stationary points that are obtained as optimization is completed to check whether the minima were real.…”
Section: Settings and Computational Methodssupporting
confidence: 93%
“…In particular, it has been found that when studying metallic clusters, the condensed Fukui functions can predict the results of nucleophilic and electrophilic interactions with poor reliability [ 105 ]. However, from the results obtained in our work, we can present four important considerations: (i) in the first place, it is not the same to obtain conclusions about the reliability of the condensed Fukui functions when studying metallic clusters or even solid systems than when considering pure organic molecules, as happens in our case; (ii) the reliability of the results that we have obtained is impressive because the condensed Fukui functions (and thus the dual descriptor) have been calculated using two different schemes for the partition of the electronic density (i.e., the atomic charges), and the same has been done for the Parr functions: the conclusions about the reaction sites are exactly the same; (iii) in our work, we considered and presented the calculation of the dual descriptor rather than the condensed Fukui functions, and it has been shown by Martínez-Araya that the dual descriptor is more reliable for predicting the electrophilic and nucleophilic sites than the condensed Fukui functions [ 106 ]; (iv) as we have shown in several previous works [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], the reliability of the conceptual DFT descriptors for predicting the reactive sites of a given molecular system is heavily dependent on the goodness of the model chemistry employed for the calculations where we understand for goodness the ability to fulfill the KID procedure mentioned in the Introduction section.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…One of these isolated molecules is named by the acronym BISARG and together with its protonated derivative, BISARG(p) have been experimentally studied as a part of a work related to the formation of melanidins (Hofmann, 1998 ) and we believe that it could be of interest to study their molecular reactivity by using the ideas of Conceptual DFT, in the same way of our previous works (Alvarado-González et al, 2013 ; Cervantes-Navarro and Glossman-Mitnik, 2013 ; Glossman-Mitnik, 2013a , b ; Martínez-Araya et al, 2013a , b ; Salgado-Morán et al, 2013 ; Glossman-Mitnik, 2014a , b , c , d ; Martínez-Araya and Glossman-Mitnik, 2015 ; Martínez-Araya et al, 2015 ; Soto-Rojo et al, 2015 ; Frau et al, 2016a , b , c ; Mendoza-Huízar et al, 2016 ; Frau et al, 2017a , b , c , d , e ; Frau and Glossman-Mitnik, 2017a , b , c , d , e , f , g ; Sastre et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%